Nano-silicon and sodium mitigate damage by potassium deficiency in chicory - Alves, Deyvielen Maria Ramos [UNESP]; de Mello Prado, Renato [UNESP]; Barreto, Rafael Ferreira; da Silva Carvalho, Lívia Tálita [UNESP] (Springer Nature, 2024)
Chicory is a food with high nutritional. The use of beneficial elements in plants, such as sodium (Na) and silicon (Si), may be important to mitigate nutritional disorders, such as potassium (K) deficiency, but research is lacking on this topic. The objective was to evaluate the effects of sodium and nano-silicon on the nutritional, physiological, growth, and quality parameters of chicory under K deficiency and sufficiency. We used a concentration for sufficient K (3.0 mmol L−1), K-deficiency (1.5 mmol L−1), combined with the lack or presence of Na (2.0 mmol L−1) and Si (2.0 mmol L−1). The experiment was carried out in a greenhouse with six treatments corresponding to K sufficiency, K-sufficiency with Na, K-sufficiency with Si, K deficiency, K-deficiency with Na, and K-deficiency with Si, with six replications. The following growth variables were evaluated: (i) plant height, (ii) stem diameter, (iii) number of leaves, (iv) leaf area, and (v) plant biomass. Potassium and Si contents in the above ground part and K utilization efficiency were assessed, and the accumulation of K, Na, and Si was calculated. The efficiency of the quantum yield of photosystem II (Fv/Fm) and the photosynthetic pigments was determined. Electrolyte leakage index and relative water content, as well as phenolic compounds, ascorbic acid, and leaf firmness index were also determined. We found that supplying nano-Si and Na to a K-deficient nutrient solution increased K accumulation by 60% and 50% and K use efficiency by 79% and 62% compared to plants without supply of those elements. Nano-Si reduced electrolyte leakage, being 41% less than Na in K-deficient chicory. However, when Na was added to a nutrient solution with sufficient potassium, the K use efficiency decreased by 48% compared to sufficient potassium without Na. Under the same condition of sufficient supply of potassium and Na, K accumulation decreased by 20% in chicory compared to sufficient potassium without Na, and the photosynthetic pigments—total chlorophyll and carotenoids—were reduced by 5% and 10%, respectively. Our findings contribute to improve cultivation systems with low supply of K as the supply of Na and nano-Si mitigates the damage caused to the metabolism of chicory under K deficiency.
Keywords: Antioxidants; Beneficial element; Bioactives; Cichorium endivia; Vegetable quality